The potential impacts of climate and forest changes on streamflow for micro-, meso- and macro-scale catchments in Norway - Shaochun Huang; Stephanie Eisner; Wai Kwok Wong; Nicolas Cattaneo (Journal of Hydrology: Regional Studies)
Study region: Six forest dominant catchments in Norway: two are micro- (< 10 km2), two are meso- (< 1000 km2) and two are macro-scale (> 10000 km2) catchments. Study focus: This study focuses on the combined climate and forest impacts on streamflow, hydrological components as well as flood and low flow levels. In addition, the relative contributions of climate and forest impacts are distinguished. New hydrological insights for the region: This study provides the first hydrological projections in Norwegian catchments driven by both the climate projections and their corresponding forest projections. Due to warmer climate and higher precipitation under the Representative Concentration Pathway scenarios (RCP2.6 and RCP4.5), continuous increase in forest timber volume is projected in five out of six catchments. The combined effects of climate and forest development lead to median changes in annual streamflow ranging from −2 % to 8 %. Climate is the major driver of streamflow changes, and forest growth slightly offsets the increase in streamflow caused by climate and reduces runoff generation locally. Forest growth reduces the flood levels caused by climate by up to 3 % in all catchments except one with large clear-cutting areas. Forest growth leads to increase in low flow levels in three coniferous forest dominant catchments while it aggravates the low flow conditions in the catchments with high coverage of deciduous forest in the summer half-year.